Three new species and new records of Ladoffa from Panama (Insecta: Hemiptera: Cicadellidae: Cicadellinae) - Lozada, Pedro W. (2010)
Three new Panamanian species of the genus Ladoffa: woldai Lozada & Freytag sp.nov., lamasi Lozada & Freytag sp.nov. and grandis Lozada & Freytag sp.nov., are described and illustrated herein. Likewise, new Panamanian records for the species variolaria Young, donsana Young, rubriguttata (Walker), elauta Young, dependens Young, uncata Young and trifasciata Cavichioli & Chiamolera, are reported.